Developing a stem-cell system of embryonic development organised by a morphogen signaling centre - Rossouw, Simone (Department of Human Biology, 2025)
Successful mammalian development is dependent on the precise communication and coordination from both the embryonic and extraembryonic tissues. These interactions ensures that the tissues become spatially localized within the embryo for the process of gastrulation, a pivotal event whereby the three germ layers: mesoderm, endoderm, and ectoderm are specified. Bone morphogenetic protein 4 (BMP4), secreted from the extraembryonic ectoderm is required for gastrulation to start whereby it activates downstream signaling molecules wingless inhibitor 3 (WNT3) and Nodal in a concentration dependent manner to specify both the mesoderm and endoderm. The ectoderm is formed in the absence of these signaling molecules. Together, these signaling molecules and mechanical constraints from the extracellular matrix (ECM), shape the developing embryo, although less is known about the precise mechanisms by which mechanical constraints function during gastrulation. As a result, defects within the coordination of cells and tissues during gastrulation can lead to congenital malformations and even embryonic death. The mechanisms underlying gastrulation are difficult to study in vivo, as gastrulation occurs post-implantation rendering the embryo inaccessible for direct in vivo experimentation. In vitro stem cell derived embryo-like structures called gastruloids are able to circumvent these impediments posed by in vivo research. Gastruloids form derivatives of all three germ layers in a spatially coordinated manner and resemble key in vivo aspects of gastrulation. In addition, gastruloids are formed solely from mouse embryonic stem cells, thereby providing an excellent model system to study the effects of BMP4 during gastrulation. This model is however restricted in that they exhibit limited morphogenesis and have no anterior neural structures present. Here, we incorporated bone morphogenetic protein-4 as a pulse and a spatially restricted signaling center into gastruloid culture to investigate the extent to which they can recapitulate gastrulation-like events in vitro. To investigate this, our laboratory has successfully grown mouse embryonic stem cells in a pluripotent state for extended periods of culture in defined cultured conditions. Pluripotency was assessed and confirmed by light microscopy, qPCR, and immunocytochemistry by the presence of pluripotency factors OCT4 and NANOG. Culture conditions were changed to disrupt pluripotency and direct differentiation into gastruloids following established protocols. Gastruloid formation was assessed by light microscopy to investigate morphogenesis while mRNA and protein levels of several genes required during gastrulation was evaluated by qPCR and immunocytochemistry, respectively. All gastruloids illustrated an exit in pluripotency and expressed both WNT3 and Nodal, required for the formation of the mesoderm and endoderm. Markers for the mesoderm and endoderm: SOX17, GATA6, Bra, and MIXL1 was expressed in varying levels while only gastruloids formed with a bone morphogenetic protein-4 signaling center, expressed markers for anterior neural lineages as seen by an upregulation in POU3F1, EN1, OTX2, IRX6, and SCUBE1. Interestingly, gastruloids cultured in polyethylene glycol-acrylate-sulfhydryl hydrogels had no change in morphology. Confocal imaging confirmed the localization of brachyury, a primitive streak marker in some gastruloids. Collectively, the results show that the gastruloids have the capability to undergo self-organization in a spatially coordinated manner and that bone morphogenetic protein-4 could replace the Chiron pulse in conventional gastruloid protocols to induce gastruloid formation. The incorporation of a spatially restricted signaling center illustrates the importance of concentration gradients for anterior neural induction. Finally, gastruloids grown in hydrogels illustrate that gastrulation most likely occurs from a combination of factors and events occurring together and that mechanical constraints alone are insufficient to drive morphogenesis.